HE CHARACTERISTICS OF GENETIC POLYMORPHISM OF HLA-ANTIGENS IN ACQUIRED APLASTIC ANEMIA IN CHILDREN - A A Chumak; T A Astrelina; M V Yakovleva; Lidiya L'vovna Lebedeva; L L TV Pukhlikova; Z M Dishlevaya; A N Arkhipova; M M Azova (RUDN Journal of Medicine, 2013)
This study presents the genetic polymorphism of HLA-antigens in acquired aplastic anemia (AAA) in 147 children (85 boys и 62 girls) aged 1 to 18 with. The control group is consisted of 1700 umbilical cord blood samples of healthy newborns. The genetic polymorphism of HLA was studied in groups of children with AAA, divided by gender and age. Our results revealed distinction in HLA-markers of predisposition and sustainability to AAA. Possible differences in factors of immunogenetic predisposition suggest different mechanisms involved in the development of the disease in different groups of children and reconsider the existing model of the pathogenesis of AAA.